2014
DOI: 10.1120/jacmp.v15i6.4994
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of phantom‐based and log file patient‐specific QA with complexity scores for VMAT

Abstract: The motivation for this study was to reduce physics workload relating to patient‐specific quality assurance (QA). VMAT plan delivery accuracy was determined from analysis of pre‐ and on‐treatment trajectory log files and phantom‐based ionization chamber array measurements. The correlation in this combination of measurements for patient‐specific QA was investigated. The relationship between delivery errors and plan complexity was investigated as a potential method to further reduce patient‐specific QA workload.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 40 publications
9
83
1
Order By: Relevance
“…Table 2 also supported this observation by the calculated correlation coefficients. However, these results do not agree with Agnew's data [9], reporting that the average and standard deviation of gantry angle errors were not related to the gamma index pass rates. This discrepancy may be explained by the fact that Agnew's data was based on Varian RapidArc having a different VMAT control algorithm, where the gantry speed was maintained constant or slowly varied under continuously varying dose rate [10].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Table 2 also supported this observation by the calculated correlation coefficients. However, these results do not agree with Agnew's data [9], reporting that the average and standard deviation of gantry angle errors were not related to the gamma index pass rates. This discrepancy may be explained by the fact that Agnew's data was based on Varian RapidArc having a different VMAT control algorithm, where the gantry speed was maintained constant or slowly varied under continuously varying dose rate [10].…”
Section: Discussioncontrasting
confidence: 57%
“…For example, Agnew et al reported that the correlations between the gantry angle errors and the dose accuracy were not observed [9]. In this paper, VMAT delivery accuracy has been more extensively investigated by calculating the linac dynamic parameters consisting of control errors, speeds and accelerations of gantry angles and MLC leaf positions using log files.…”
Section: Introductionmentioning
confidence: 99%
“…This software creates a report of MLC error histograms and the average RMS of MLC positioning errors. It has been previously validated for step-and-shoot IMRT, 3,8 VMAT in TrueBeams 19 and also for VMAT using Clinacs with this data set. All data were presented as median values with associated ranges (minimum and maximum).…”
Section: Methodsmentioning
confidence: 99%
“…These log files were analyzed using the in-house code. 19 This software has the ability to analyze the MLC leaf pairs in DynaLog files created using Varian Clinacs (.DLG files) and trajectory log files created by Varian TrueBeams (.INI files) compared with the planned positions defined in the plan files (digital imaging and communications in medicine). This software creates a report of MLC error histograms and the average RMS of MLC positioning errors.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for analysis and presentation of machine log files have been previously reported for linear accelerator‐(linac‐) based external beam radiation therapy (EBRT) treatments 9 , 10 , 11 , 12 , 13 . The MLC dynamic log files are available on Varian linac treatment machines (14) and have been utilized at the authors' institution and by other groups to validate the accuracy and completeness of the treatment deliveries 15 , 16 , 17 , 18 , 19 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%